2001
DOI: 10.1177/0145445501252002
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Analysis of Aggression

Abstract: Iwata, Dorsey, Slifer, Bauman, and Richman developed an assessment method to identify the operant functions of self-injurious behavior. In this study, a similar method was used to assess the operant functions of aggression displayed by children and adolescents with developmental disabilities. Although previous research has shown that aggression is an operant behavior, there has been no comprehensive analysis of aggression using analog functional analysis method. Eight children and adolescents participated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…In addition, the experimenters observed parent and child interactions to con®rm parental report of problem behavior correlates. Finally, each of the participants except Tabbatha participated in other studies involving analog functional analyses (Vollmer, Marcus, Ringdahl, & Roane, 1995;Marcus, Vollmer, Swanson, Roane, & Ringdahl, 2001). These preliminary procedures showed that Joe's and Joel's tantrums frequently occurred during demand situations, and their analog functional analyses con®rmed that escape was a reinforcer (Marcus et al, 2001).…”
Section: Interviews and Direct Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the experimenters observed parent and child interactions to con®rm parental report of problem behavior correlates. Finally, each of the participants except Tabbatha participated in other studies involving analog functional analyses (Vollmer, Marcus, Ringdahl, & Roane, 1995;Marcus, Vollmer, Swanson, Roane, & Ringdahl, 2001). These preliminary procedures showed that Joe's and Joel's tantrums frequently occurred during demand situations, and their analog functional analyses con®rmed that escape was a reinforcer (Marcus et al, 2001).…”
Section: Interviews and Direct Observationmentioning
confidence: 99%
“…Finally, each of the participants except Tabbatha participated in other studies involving analog functional analyses (Vollmer, Marcus, Ringdahl, & Roane, 1995;Marcus, Vollmer, Swanson, Roane, & Ringdahl, 2001). These preliminary procedures showed that Joe's and Joel's tantrums frequently occurred during demand situations, and their analog functional analyses con®rmed that escape was a reinforcer (Marcus et al, 2001). Roger's aggression was reinforced by contingent access to materials, such as preferred toys (Vollmer et al, 1995).…”
Section: Interviews and Direct Observationmentioning
confidence: 99%
“…Lovaas, Freitag, Gold & Kassorla, 1965;Oliver, Hall & Murphy, 2005). It has been suggested that aggression could be sensitive to positive reinforcement in the form of access to adult attention, peer attention and tangible items (Hawkins, Peterson, Schweid & Bijou, 1966;Patterson, Littman & Bricker, 1967) and Marcus, Vollmer, Swanson, Roane & Ringdahl (2001) provide empirical evidence that aggression in children with intellectual disabilities can be positively or negatively reinforced. Hanley, Iwata & McCord (2003) carried out a meta-analysis of the functional analysis of problem behavior, and found that an operant reinforcement process could be identified for 50 out of 52 studies that reported aggression in individuals with an intellectual disability .…”
Section: Introductionmentioning
confidence: 99%
“…Thus a critical component of interventions that have successfully altered children's aggressive or anti-social behaviour has been the identification and removal of those consequences that reinforce the target behaviour [e.g., Broussard and Northup, 1997;DeLeon et al, 2000;Fowler et al, 1986;Marcus et al, 2001].…”
mentioning
confidence: 99%